2023
DOI: 10.1038/s41467-022-35719-y
|View full text |Cite
|
Sign up to set email alerts
|

An entosis-like process induces mitotic disruption in Pals1 microcephaly pathogenesis

Abstract: Entosis is cell cannibalism utilized by tumor cells to engulf live neighboring cells for pro- or anti-tumorigenic purposes. It is unknown whether this extraordinary cellular event can be pathogenic in other diseases such as microcephaly, a condition characterized by a smaller than normal brain at birth. We find that mice mutant for the human microcephaly-causing gene Pals1, which exhibit diminished cortices due to massive cell death, also exhibit nuclei enveloped by plasma membranes inside of dividing cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(33 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Because many microcephaly-causing genes encode proteins that are involved in faithful mitosis, studying how mitotic defects lead to microcephaly builds a greater understanding of overall microcephaly pathogenesis (Frank et al, 2000;McConnell et al, 2004;Silver et al, 2010;Chen et al, 2014;Insolera et al, 2014;Faheem et al, 2015;Marjanovic et al, 2015;Mao et al, 2016;Bianchi et al, 2017;Sgourdou et al, 2017;Little and Dwyer, 2019;Shi et al, 2019;McNeely and Dwyer, 2020;Phan et al, 2021;White et al, 2021;Martins et al, 2022;Sterling et al, 2023). In this study, cellular analysis of BubR1 cKO cortices identified a spectrum of structural abnormalities in chromosomes that are caused by the functional loss of BubR1.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Because many microcephaly-causing genes encode proteins that are involved in faithful mitosis, studying how mitotic defects lead to microcephaly builds a greater understanding of overall microcephaly pathogenesis (Frank et al, 2000;McConnell et al, 2004;Silver et al, 2010;Chen et al, 2014;Insolera et al, 2014;Faheem et al, 2015;Marjanovic et al, 2015;Mao et al, 2016;Bianchi et al, 2017;Sgourdou et al, 2017;Little and Dwyer, 2019;Shi et al, 2019;McNeely and Dwyer, 2020;Phan et al, 2021;White et al, 2021;Martins et al, 2022;Sterling et al, 2023). In this study, cellular analysis of BubR1 cKO cortices identified a spectrum of structural abnormalities in chromosomes that are caused by the functional loss of BubR1.…”
Section: Discussionmentioning
confidence: 72%
“…Distinguishing P53 activation as a molecular mechanism for microcephaly pathology in various models provides important insight into cellular defects linked to P53 activation. For instance, when P53 activation is directly associated with mitotic defects, genetic deletion or inhibition of P53 can substantially rescue the microcephaly phenotype (Sterling et al, 2023). Alternatively, when P53 elimination solely promotes cell survival, a variety of outcomes can be observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, entosis appears to select for relative setpoints of mechanical tension in cell populations by mediating the clearance of cells with high tension by those with lower tension. In noncancer tissues, this effect may eliminate dysfunctional cells and act in a tumor-suppressive manner, for example, through a clearly established function to eliminate cells exhibiting aberrant mitosis 27 , 31 , 61 or defective polarity 23 , 61 , as well as through the observed effect of entosis on limiting transformed growth 1 , 62 . Tumor-suppressive activity has also been shown in a zebrafish model where entotic internalization was shown to limit the growth of epidermal hyperplasia 63 .…”
Section: Discussionmentioning
confidence: 99%